Effect of William Flexion Exercise and Core Stability Exercise on Pain in Myogenic Low Back Pain - Isidorus Jehaman; Maria Yuliana Diaz Yanto; Redi Tantangan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Low back pain myogenic is pain around the lower back caused by disorders or abnormalities in the elements of the muscles and tendons without neurological disorders. Low back pain myogenic is a pain syndrome that occurs in the lower back region with the main cause being muscle. The causes of low back pain are myogenic in addition to excessive muscle work can also occur due to poor postures such as kyphosis, lordosis, scoliosis, round back, and flatback. If a muscle is injured and if it is not treated immediately, spinal spasms occur which can cause complaints of pain in the lower back area. This type of research uses a quasi-experimental two groups pre-test and post-test design, which aims to determine the difference between the intervention of the William flexion exercise and core stability exercise on patients with low back pain myogenic. The samples in this study were all patients with a diagnosis of low back pain myogenic who came to the Nagi Larantuka Public Health Center in 2022. The number of samples in this study were 24 people who were divided into two groups, each group consisting of 12 respondents. Based on the results of the different test results using the Mann Whitney test between the William Flexion Exercise and Core Stability Exercise groups, it is known that the P value is 0.284> 0.05. These results indicate that there is no significant difference between the measurement results between the William flexion exercise and core stability exercise groups. Because there is no difference, it can be concluded that the William flexion exercise and core stability exercise both affect patients with low back pain myogenic.